2001
DOI: 10.2166/wst.2001.0742
|View full text |Cite
|
Sign up to set email alerts
|

Early warning of faecal contamination of water: a dual mode, automated system for high- (<1 hour) and low-levels (6-11 hours)

Abstract: There is a recognised need for methods that permit rapid estimation of the sanitary quality of water e.g. during raw water monitoring and emergencies involving water treatment failure or main breaks in a distribution network. In this study, two models for predicting the level of faecal contamination of water were studied. The first format, based on measurement of beta-galactosidase activity by the automated Colifast analyser, detected faecal contamination of high levels, corresponding to > 15 thermotolerant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…They are simple to perform and do not require expensive instrumentation. Such assays are in demand for risk assessment of water supply systems for early warning of high FC concentrations, for example by monitoring of raw water quality (Tryland et al 2001), assessment of treatment efficiency, monitoring of finished water quality as well as recreational waters. They also have been recently exploited for daily monitoring of beach water quality .…”
Section: Application Of Rapid Enzymatic Assays For Bacterial Detectionmentioning
confidence: 99%
“…They are simple to perform and do not require expensive instrumentation. Such assays are in demand for risk assessment of water supply systems for early warning of high FC concentrations, for example by monitoring of raw water quality (Tryland et al 2001), assessment of treatment efficiency, monitoring of finished water quality as well as recreational waters. They also have been recently exploited for daily monitoring of beach water quality .…”
Section: Application Of Rapid Enzymatic Assays For Bacterial Detectionmentioning
confidence: 99%
“…In the present study, we evaluated a rapid and simple enzyme based bioluminescence procedure for detection of coliform bacteria in drinking water (ColiLight). The enzyme b-D-galactosidase has been targeted in a range of colorimetric and fluorometric assays focusing on coliform bacteria in water and food (Apte et al 1995;Van Poucke and Nelis 1995;Geisler et al 2000;George et al 2001;Tryland et al 2001;Van Poucke and Nelis 2000). However, enzyme assays based on luminescence have the potential to be more sensitive than detection methods based on chromogenic of fluorogenic substrates (Bronstein et al 1989;Van Poucke and Nelis 1995;Masuda-Nishimura et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, one E. coli cell can easily divide and reach the detection limit for bioluminescence detection of b-D-galactosidase activity within 4 h. Hence, an enrichment time of 6-8 h should be sufficient to allow detection of E. coli and other coliforms with comparable b-D-galactosidase activity. An incubation time of 6 h or more has also been used in other assays for ''rapid detection'' of low-level concentrations of coliforms in environmental samples (Masuda-Nishimura et al 2000;Tryland et al 2001;Van Poucke and Nelis 2000;Serra et al 2005). Van Poucke and Nelis (2000) evaluated a range of enzymatic methods for detection of E. coli and other coliforms, and concluded that most methods requires at least 5.5-6.5 h for detection of indicator bacteria on membrane filters.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of selective growth and GAL activity ensure the specificity of such methods [14]. By using sensitive instruments for detection of the end product, GAL activity can also often be measured directly in contaminated environmental water samples without pre-cultivation [15]. Such direct measurement of GAL activity in a water sample is not a measurement of culturable coliform bacteria, but of all enzymes (compounds that may hydrolyze the actual substrate) initially present in the water samples [12,16].…”
Section: Introductionmentioning
confidence: 99%